Pengendalian Kualitas Produk Menggunakan Cumulative Sum Control (cusum) dan Fuzzy Decision Making pada Proses Produksi Buku Tahunan di CV Renjana Offset - Elly Wuryaningtyas Yunitasari; Esti Dwi Pujaningsih; Emmy Nurhayati (Proklamasi 45 University, 2025)
CV Renjana Offset is a printing company that produces yearbooks for export. In the production process, various types of rejects were found in the pack products, such as scratches, glue, tears, and problematic pop-ups, as well as in book products, such as reversed arrangement, broken threads, and shadows. This study uses the Cumulative Sum Control (CUSUM) method to analyze product quality and the Fuzzy Analytic Hierarchy Process (FAHP) to determine improvement priorities. The results showed an average reject of 3.96% with a total of 35.66% from November 2023 to July 2024, although there was an increase to 4.74% in July 2024. The cumulative CUSUM of 0.143 units with a monthly average of 0.016 units indicates consistent quality, but improvements are needed in operators and materials. The proposed improvements aim to reduce rejects and improve quality through structured and sustainable improvement actions.